Assistance in Book-keeping and Digital Marketing Training for Serati Ayu Yadnya Group, Banjar Pande, Desa Adat Sempidi, Mengwi, Badung - Sariani, Ni Ketut; Sudarmini, Ketut; Jayanthi, Luh Gede Pande Eka Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
In line with contemporary developments, women today, both in urban and rural areas, often take on multiple roles due to expanded opportunities for self-development. In Bali, where Hindu cultural and religious practices are prevalent, this trend has led to the formation of groups like Serati, who create ceremonial offerings (banten). The Serati Ayu Yadnya group in Desa Adat Sempidi, coordinated by Ayu Made Trisnawati, has met local demand through cooperation with other Serati groups. To boost their income and expand market reach via digital marketing, they need accurate accounting practices. Therefore, training in accounting book-keeping and digital marketing was conducted for the Serati Ayu Yadnya group in Banjar Pande, Desa Adat Sempidi, Mengwi, Badung